Effects of nutritional supplementation during off-season college football training on body composition and strength - Kreider, R. B.; Klesges, R. C.; Lotz, D.; Davis, M.; Cantler, E.; Grindstaff, P.; Ramsey, L.; Bullen, D.; Wood, L.; Almada, A. (Journal of Exercise Physiology online, 1999)
Athletes often supplement their diet with meal-replacement/weight gain powders in an attempt to increase muscle mass and strength. However, it is unclear whether these supplements affect lean tissue accretion and/or strength gains. This study evaluated whether supplementing the diet with commercially available nutritional supplements during 84 days of winter resistance/agility training and spring football practice affects body composition and/or strength alterations. In a double blind and randomized manner, 51 college football players were matched and randomly assigned to supplement their diet with either a carbohydrate placebo (P), a vitamin/mineral fortified carbohydrate/protein supplement (Met-RxTM), a vitamin/mineral fortified carbohydrate/protein powder containing 20 g/day of creatine (PhosphagainTM), or a vitamin/mineral fortified carbohydrate/protein powder containing 25 g/day of creatine (Phosphagain 2TM). Additionally, a group of 10 subjects maintained normal dietary practices during training and served as non-supplemented controls (NS). Total body weight, total body water, DEXA determined body composition, and isotonic strength tests were assessed on days 0, 35, and 84 of training. Results revealed that mean gains in soft tissue/lean mass were significantly greater in the PhosphagainTM (P-I) and Phosphagain 2TM (P-II) groups than changes in the NS, P, and Met-RxTM (MRx) groups (NS 0.7±1.3; P 1.2±1.6; MRx 0.8±1.2; P-I 2.3±1.4; P-II 3.4±1.8 kg). Mean gains in 1 RM bench press in the MRx, P-I and P-II groups were significantly greater than gains observed in the NS group (NS 2.0±9; P 7.6±7; MRx 9.8±6; P-I 10.3±5; P-II 10.0±8 kg). Results indicate that P-I and P-II supplementation during training promoted greater gains in lean tissue mass in comparison to NS, P, and MRx groups and that gains in strength in the supplemented groups were greater than the NS group.